2013
DOI: 10.1149/05801.0919ecst
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Gas Diffusion Layers in PEM Fuel Cells during Drive Cycle Operation

Abstract: Polymer electrolyte membrane (PEM) fuel cells show voltage degradation when subjected to long-term drive cycle operation. While the kinetic losses in the fuel cells can be assigned to catalyst layer degradation, there is a significant mass transport loss of up to 100mV at 2 A/cm2 in 400 hours of operation. This mass transport loss can be attributed to the Gas Diffusion Layer (GDL) degradation especially when using low surface area carbon based catalyst materials. Ex situ ageing studies where the GDL is oxidize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Polarization curves were recorded with both decreasing and increasing 44 and Spernjak et al 42 Ex situ and in situ durability tests were performed on the BC GDL. The ex situ aging was performed using an accelerated test developed under the DECODE project, 45 which consisted of boiling in a 30% H 2 O 2 solution at 95 °C for up to 15 h. 46 The in situ durability testing was performed using a portion of the USDRIVE Fuel cell Tech Team (FCTT) durability protocol, 47 which consisted of cycling between 0.02 A cm −2 (30 s) and 1.2 A cm −2 (30 s) at 80 °C, 113% RH, and 101.3 kPa.…”
Section: Methodsmentioning
confidence: 99%
“…Polarization curves were recorded with both decreasing and increasing 44 and Spernjak et al 42 Ex situ and in situ durability tests were performed on the BC GDL. The ex situ aging was performed using an accelerated test developed under the DECODE project, 45 which consisted of boiling in a 30% H 2 O 2 solution at 95 °C for up to 15 h. 46 The in situ durability testing was performed using a portion of the USDRIVE Fuel cell Tech Team (FCTT) durability protocol, 47 which consisted of cycling between 0.02 A cm −2 (30 s) and 1.2 A cm −2 (30 s) at 80 °C, 113% RH, and 101.3 kPa.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, it may be stated that a more homogeneous current density distributions would likely extend the life time of the fuel cell, as mentioned in [23,24]. It should be noted that the water management is influenced by many effects, e.g., water removal due to high reactant flow rate [25] or GDL oxidation by substances as hydrogen peroxide and sulfuric acid degrades fuel cell operation [16,26].…”
Section: Resultsmentioning
confidence: 99%
“…Especially for automotive PEMFC applications (operating with high current density), novel two-component MPLs including carbon black and multi-wall carbon nanotubes (MWCNTs) were shown to provide superior properties in terms of high current capability 12), 13) while being regarded as potentially beneficial with regard to MEA durability 14) . Synergy effects with respect to conductivity and a modified pore size distribution are seen as the main factors accounting for higher fuel cell performance 15) . A recent study also revealed that hydrophilic SWCNTs are very effective MPL additives for the dry operation of PEMFCs 16) .…”
Section: Micro-porous Layer Carbon Materialsmentioning
confidence: 99%